PENGARUH DANA ZIS DAN INFLASI TERHADAP TINGKAT KEMISKINAN DENGAN PERTUMBUHAN EKONOMI SEBAGAI VARIABEL INTERVENING - Salsa Amanda (2023)
The decrease in the poverty rate in Indonesia over the past decade has been no more than 1 percent, which is in the range of 0.1 to 0.8 percent, which shows that poverty alleviation in Indonesia has not been too significant. The purpose of this study is to analyze the influence of ZIS funds and inflation on poverty rates in Indonesia by mediating economic growth. The analysis method used is path analysis as an advanced model of multiple linear regression. The results shows that ZIS funds have a significant direct influence on the poverty rate, while inflation and economic growth do not have a significant direct influence on the poverty rate. Then the ZIS fund variables and inflation do not have a significant direct influence on economic growth. In indirect effect testing, economic growth cannot mediate the effect of ZIS funds and inflation on poverty significantly.